Relationship between four healthy lifestyle factors and all-cause and cardiovascular disease mortality among residents aged 35 – 75 years in Hebei province - Yuhuan LIU; Lijuan TANG; Xiaoying LU; Jingjing ZHAO; Yajing CAO; Xiaoli LIU; Dongsheng JIANG (Zhongguo gonggong weisheng)
ObjectiveTo investigate the relationship between four healthy lifestyle factors and all-cause and cardiovascular disease (CVD) mortality among residents aged 35 – 75 years in Hebei province, and to provide scientific evidence for promoting healthy lifestyles. MethodsData were collected from 48 377 residents aged 35 – 75 years in 11 districts and counties of Hebei province (Daming county, Handan city; Qinghe county, Xingtai city; Xuanhua district, Zhangjiakou city; Yuhua district, Shijiazhuang city; Chengde county, Chengde city; Sanhe city, Langfang city; Quyang county, Baoding city; Huanghua city, Cangzhou city; Shenzhou city, Hengshui city; Zunhua city, Tangshan city; and Funing district, Qinhuangdao city) who participated in the National Early Screening and Comprehensive Intervention Program for High-Risk Populations of CVD from September 2016 to December 2022. These participants had complete information on four healthy lifestyle factors (non-smoking, no or moderate alcohol consumption, adequate physical activity, and a healthy diet) and socio-economic characteristics, and no history of CVD or cancer. Mortality data were obtained by linking with the cause-of-death surveillance platform, with follow-up until December 31, 2022. Multivariable Cox proportional hazards regression models were used to analyze the relationship between the four healthy lifestyle factors and all-cause and CVD mortality. ResultsAmong the 48 377 residents aged 35 – 75 years included in the analysis, 39 513 (81.68%), 47 026 (97.21%), 10 040 (20.70%), and 6 606 (13.66%) adhered to non-smoking, no or moderate alcohol consumption, adequate physical activity, and a healthy diet, respectively. Only 1 360 (2.81%) adhered to all four healthy lifestyle factors. By December 31, 2022, there were 878 (1.81%) all-cause deaths and 478 (0.99%) CVD deaths. Among those adhering to non-smoking, no or moderate alcohol consumption, adequate physical activity, and a healthy diet, there were 629 and 346, 847 and 463, 153 and 85, and 88 and 48 all-cause and CVD deaths, respectively, with corresponding mortality rates of 1.59% and 0.88%, 1.8% and 0.98%, 1.52% and 0.85%, and 1.33% and 0.73%. Among residents with 0, 1, 2, 3, and 4 healthy lifestyle factors, there were 18 and 9, 171 and 88, 528 and 294, 154 and 82, and 7 and 5 all-cause and CVD deaths, respectively, with corresponding mortality rates of 2.86% and 1.43%, 2.79% and 1.43%, 1.81% and 1.01%, 1.39% and 0.74%, and 0.51% and 0.37%. After adjusting for potential confounders including sex, age, education level, marital status, occupation, annual household income, residence, and social health insurance, multivariable Cox proportional hazards regression analysis showed that adherence to adequate physical activity and a healthy diet was associated with a 26% (HR = 0.74, 95%CI: 0.61 – 0.90) and 24% (HR = 0.76, 95%CI: 0.60 – 0.96) lower risk of all-cause mortality, respectively, compared to non-adherence. Adherence to all four healthy lifestyle factors was associated with a 74% (HR = 0.26, 95%CI: 0.11 – 0.63) lower risk of all-cause mortality compared to non-adherence to any of the four factors. ConclusionsThe adherence rates to the four healthy lifestyle factors were low among residents aged 35 – 75 years in Hebei province. Adherence to adequate physical activity, a healthy diet, and all four healthy lifestyle factors can reduce the risk of all-cause mortality.